Integration and partial excision of a cryptic plasmid in Pseudomonas syringae pv. phaseolicola. - Curiale, M S (1982)
A virulent strain of Pseudomonas syringae pv. phaseolicola, a pathogen of the common bean Phaseolus vulgaris (L.), was shown to harbor a 98-megadalton cryptic plasmid, pMC7105. After exposure of this strain to the plasmid-curing agent mitomycin C, a colony was isolated which had no detectable extrachromosomal DNA. Hybridization of labeled pMC7105 probe to nitrocellulose filters containing Southern-blotted BamHI cleavage products of cellular DNA revealed that pMC7105 was integrated into the chromosome rather than cured from this strain. Imprecise excision of pMC7105 resulted in the formation of three smaller plasmids of 34, 50, and 58 megadaltons. BamHI and EcoRI fingerprint analyses revealed that these plasmids were excised from a common region of pMC7105. The BamHI fragments of pMC7105 which were not present in the excision plasmids remained integrated and could be detected by hybridization of pMC7105 probe to Southern-blotted cellular DNA from these strains. Certain chromosomal fragments also had homology with the pMC7105 probe. The excision plasmids were stably maintained and neither integration nor excision altered the pathogenicity of these strains.